Fourth International Bridge Engineering Conference [proceedings] : San Francisco, California, August 28-30, 1995 - International Bridge Engineering Conference 1995 San Francisco, Calif.); National Research Council (U.S.). Transportation Research Board (Washington, D.C. National Academy Press, 1995)
Conference sessions cover: bridge management systems, bridge aesthetics, bridge performance, bridge construction, long-span bridges, bridge loads and dynamics, FRP composites and other materials, bridge rehabilitation, seismic response of bridges, bridge bearings, joints, and details, prestressed concrete bridges, bridge structural systems, bridge substructures: scour and ship impact, bridge fatigue and redundancy, and wood bridges. -- Intro., p.xi.
Transportation Research Board, National Research Council.
Volume 1
Includes bibliographical references.
Keywords: Bridges -- Congresses; Bridges -- Design and construction -- Congresses; Bridges -- Maintenance and repair -- Congresses; Bridges -- Live loads -- Congresses; Bridges -- Earthquake effects -- Congresses